A numerical investigation of isobaric combustion strategy in a compression ignition engine. (November 2021) - Liu, Xinlei; Aljabri, Hammam; Mohan, Balaji; Babayev, Rafig; Badra, Jihad; Johansson, Bengt; Im, Hong G
Three-dimensional computational fluid dynamic simulations were conducted to study the means to achieve isobaric combustion mode in a compression ignition engine, which is intended to be used in the high-efficiency double compression-expansion engine (DCEE) concept. Compared to the conventional diesel combustion mode, the isobaric combustion mode generated a significantly lower peak combustion pressure, which was beneficial for the high load extension. For both combustion modes, the ignition was triggered downstream of the nozzle, with the heat release dominated by HCO + O2  = CO+HO2, while the injection-combustion duration for the isobaric combustion mode was significantly longer. The effects of swirl ratio, spray angle, and piston geometries on the isobaric combustion at various engine loads were also investigated. The higher swirl ratio resulted in a higher heat transfer loss and thus lower thermal efficiency. Due to the higher air utilization rates and lower heat transfer losses, cases with spray angles of 140° and 150° generated the higher thermal efficiencies. The piston bowl geometry was found to have a significant impact on the mixing and combustion processes, especially at high engine load conditions. For the conditions under study, the original piston geometry with a swirl ratio of 0 and a spray angle of 140° demonstrated the highest thermal efficiency for the isobaric combustion mode. The results of this work will provide guidance in the practical design and implementation of the DCEE concept.